Magnetic Resonance Imaging Analysis of Rotational Alignment in Patients With Patellar Dislocations. (January 2013) - Diederichs, Gerd; Köhlitz, Torsten; Kornaropoulos, Evgenios; Heller, Markus O.; Vollnberg, Bernd; Scheffler, Sven
Background: The role of anatomic risk factors in patellofemoral instability is not yet fully understood, as they have been observed in patients either alone or in combination and in different degrees of severity. Purpose: To prospectively analyze rotational limb alignment in patients with patellofemoral instability and in controls using magnetic resonance imaging (MRI). Study Design: Cross-sectional study; Level of evidence, 3. Methods: Thirty patients (mean age, 22.9 y; range, 12-41 y) with a history of patellar dislocation and 30 age- and sex-matched controls (mean age, 25.2 y; range, 16-37 y) were investigated. The patients underwent MRI of the leg at 1.5 T using a peripheral angiography coil and a T2-weighted half-Fourier acquisition single-shot turbo spin echo (HASTE) sequence for measuring femoral antetorsion, tibial torsion, knee rotation, and mechanical axis deviation (MAD). The mean values of these parameters were compared between patients and controls. In addition, the patients underwent an assessment to determine the influence of rotational limb alignment on lateral trochlear inclination, trochlear facet asymmetry, trochlear depth, Insall-Salvati index, and tibial tuberosity–trochlear groove distance. Results: Patients had 1.56-fold higher mean femoral antetorsion (20.3° ± 10.4° vs 13.0° ± 8.4°; P < .01) and 1.6-fold higher knee rotation (9.4° ± 5.0° vs 5.7° ± 4.3°; P < .01) compared with controls. Moreover, patients had 2.9 times higher MAD (0.81 ± 0.75 mm vs −0.28 ± 0.87 mm; P < .01). Differences in tibial torsion were not significant. Also, there were no significant correlations between parameters of rotational alignment and standard anatomic risk factors. Conclusion: Our results suggest that some patients with nontraumatic patellar instability have greater internal femoral rotation, greater knee rotation, and a tendency for genu valgum compared with healthy controls. Rotational malalignment may be a primary risk factor in patellar dislocation that has so far been underestimated.